Double Strain‐Promoted Macrocyclization for the Rapid Selection of Cell‐Active Stapled Peptides. Issue 51 (2nd November 2015) - Lau, Yu Heng; Wu, Yuteng; Rossmann, Maxim; Tan, Ban Xiong; de Andrade, Peterson; Tan, Yaw Sing; Verma, Chandra; McKenzie, Grahame J.; Venkitaraman, Ashok R.; Hyvönen, Marko; Spring, David R.
Abstract: Peptide stapling is a method for designing macrocyclic alpha‐helical inhibitors of protein–protein interactions. However, obtaining a cell‐active inhibitor can require significant optimization. We report a novel stapling technique based on a double strain‐promoted azide–alkyne reaction, and exploit its biocompatibility to accelerate the discovery of cell‐active stapled peptides. As a proof of concept, MDM2‐binding peptides were stapled in parallel, directly in cell culture medium in 96‐well plates, and simultaneously evaluated in a p53 reporter assay. This in situ stapling/screening process gave an optimal candidate that showed improved proteolytic stability and nanomolar binding to MDM2 in subsequent biophysical assays. α‐Helicity was confirmed by a crystal structure of the MDM2‐peptide complex. This work introduces in situ stapling as a versatile biocompatible technique with many other potential high‐throughput biological applications. Abstract : More strain, more gain : A strained cyclodialkyne was used to staple diazidopeptides directly in the medium of a cell culture assay. This in situ approach is simple to conduct and enables combined stapling and screening for cell‐active stapled peptides in a parallel, high‐throughput format. The method was applied to the p53/MDM2 interaction as proof of principle, and a new inhibitor was identified and its crystal structure with MDM2 obtained.